THE INFLUENCE OF DIGITAL TECHNOLOGY ON STUDENTS’ MOTIVATION IN LEARNING ENGLISH SPECIFIC PURPOSE - Idaryani Idaryani; Fidyati Fidyati (Journal of English Language and Education, 2021)
The rapid growth of sophisticated technology has provoked a new way of teaching ESP. These digital technologies in some way enable the teachers to design teaching material more interesting as learning ESP is designed based on the students' needs related to the future professional workplace setting. Moreover, by adopting digital technology into the teaching classrooms, the student can find learning material easily and efficiently. Therefore, this research aims to find out the following issues: 1) what are the preferable digital tools used in learning ESP, and how they work in the classroom? 2) how do those tools influence the students’ motivation in learning ESP? This research employs a library research approach by examining a few related articles on the implementation of digital technology in ESP classrooms, and its impact on students in learning ESP. The result of the study shows that integrating digital technology in classroom ESP is beneficial. Students are more interactive, the teaching class is more collaborative and it can improve learner proficiency. Moreover, integrating digital technology in teaching ESP can create an enjoyable teaching-learning process, result in a positive attitude of the learners, to be motivated therefore the students are more involved in learning activities. However, the study also confirms that adopting digital technology in ESP classrooms also have some drawbacks, for instance, students are easy to be distracted or get digressed when using digital technology such as youtube or smartphone in the learning process.